PENGARUH TEKNIK INVESTIGASI ROLE PLAYING TERHADAP KETERAMPILAN BERMAIN DRAMA PADA SISWA KELAS XI SMKN 4 MEDAN - Jihan Aqilah Zahra; Muharrina Harahap (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2024)
This research aims to find out how class XI students at SMKN 4 Medan are able to play drama before using the Role Playing technique, to find out how the drama playing skills of class This research is classified as quantitative research with the type of experimental research. The design in this research uses _One Group pre-test and post-test design which only uses one group, namely the experimental group. This experimental group was given a pre-test before being given treatment to find out the situation before being given treatment and after receiving treatment they were given a post-test to find out the situation afterwards. In this way, the treatment results obtained are more accurate because they can be compared with the situation before the treatment was given. Based on the results of descriptive analysis, the average score for class drama playing ability was 30.8, the highest score was 22 and the lowest score was 16, after using the role play technique or in the first test it was in the poor category. The average value is 81.65%, the highest value is 52 and the lowest value is 46, and the application of the t test to evaluate the hypothesis shows the value of t_count = -55.373, and ttable = 1.703. so the value -t_tabel>t_count is -1.703 > -55.373. This result means that Ho is rejected and Ha is accepted. This means that the Role Playing investigation technique has an effect on improving drama playing skills in class XI students at SMKN 4 Medan.